Analysis of diversity index, dominance and composition of beach seine in Masjid Raya, Aceh Besar District, Indonesia. Issue 1 (November 2021) - Chaliluddin, M A; Affan, J M; Ramayanti, R; Miswar, E; Purnama, N R; Nellyana, R; Syahputra, F
Abstract: Beach seine fishing gear is still widely used by Acehnese fishermen. Scientific information on the composition of the catch of beach seine in Lamnga and Ruyung waters is not yet available. This study aims to determine the composition of beach seine in Lamnga Village and Ruyung waters. Data collection is carried out by following the operation of the beach seine unit with ten days of data collection at each station. The research data were in the form of type and weight of fish caught and analyzed descriptively. The results of the measurement of the fishing gear of the beach seine obtained that the fishing gear at station I was smaller than station II. Analysis of the composition of the catch of beach seine at station 1 obtained 38 species consisting of 43, 447 fish, which was dominated by shortfin scads fish of 529.98 kg. While at station II, 32 species were obtained with a total of 17, 511 fish, which was dominated by shortfin scads fish of 648.90 kg. The results of the analysis showed that the catches of beach seine at station I were higher both in terms of the number of species and catch weights compared to station II.